Structural and chemical features of potash feldspars from pegmatites of the Lipovskoe vein field (Middle Urals) - Zakharov Anatoliy Vladimirovich; Galakhova Olga L'Vovna (Федеральное государственное бюджетное образовательное учреждение высшего образования «Уральский государственный горный университет», 2017)
The authors studied structural and chemical properties of the potassium feldspars from different types of granitic pegmatites of Lipovskiy vein field, located 70 km northeast of Ekaterinburg city, in vicinity of the Lipovskoe village. These pegmatites gained worldwide fame at the beginning of the last century because of the active extraction of pink tourmalines (rubellites). For the study authors selected potassium feldspars from two types of granitic pegmatites conventional and contaminated (desensitized granite veins were untested, as potassium feldspars are absent in them). According to the powder roentgenometry, orthoclase and intermediate microcline were only in normal granitic pegmatites, and intermediate and maximum microcline in lithium-bearing contaminated veins. Microprobe analysis of the potassium feldspars also showed variability in their chemical composition from the structural ordering of minerals. Microclines and orthoclases from the ordinary pegmatites are enriched by sodium and depleted by cesium and rubidium, and potassium feldspars from the lithium-bearing veins, on the contrary, are depleted by sodium and enriched by rare alkaline elements. Authors established that at increase of the contents of Rb and Cs there is an increase of the degree of triclinity of the potassium feldspars, i.e. in substantially pure (maximum) microcline forms in the contaminated pegmatites of Lipovskiy vein field. An interesting fact is the drastic decrease in the number of perthite intergrowths of albite in a matrix of potassium feldspar from the contaminated pegmatites compared to conventional granite veins. In many samples of microcline from the contaminated pegmatites, perthite intergrowths are visually absent and, apparently, make up microperthite intergrowths.
Keywords: КАЛИЕВЫЙ ПОЛЕВОЙ ШПАТ; ГРАНИТНЫЕ ПЕГМАТИТЫ; ЛИПОВСКОЕ ЖИЛЬНОЕ ПОЛЕ; СРЕДНИЙ УРАЛ; POTASSIUM FELDSPAR; GRANITIC PEGMATITES; LIPOVSKOE VEIN FIELD; MIDDLE URALS; 549.651(470.5)